The Relationship Between Toxoplasmosis and Concentration of Prolactin and Progesterone in Pregnant Women - Alshammary, Amal F.; Alanazi, Basil; Alghamdi, Suad; Aldosari, Sahar; Aljohani, Manal M.; Alanazi, Essa E.; Alahmari, Ali A; Almatrrouk, Shaihana; Alonazi, Fahad N.; Alanazi, Mona; Aldahish, Afaf; Alshaikh, Sana; et al. (International Journal of Innovative Research in Medical Science, 2024)
Toxoplasma gondii (T.gondii) is an intracellular protozoon that causes toxoplasmosis in one-third of the world's population. During pregnancy, the prevalence of toxoplasmosis rises during the second and third trimesters causing abortion and a mild mononucleosis-like syndrome. Normally, progesterone rises during pregnancy, but in the case of toxoplasmosis, the body raises prolactin to inhibit T. gondii. The present study investigated the relationship between Toxoplasma gondii infection (toxoplasmosis) and the concentration of both prolactin and progesterone in infected pregnant women. A systematic review approach was conducted to research the aim of this study. PubMed, Scopus, Web of Science, and Google Scholar were searched using the following keywords “Toxoplasma gondii” or “T.gondii” AND “protozoon” OR “toxoplasmosis” OR “animals” OR “prolactin” OR “progesterone.” Only primary studies were included, whereas reviews and non-experimental studies were excluded. Six studies met the inclusion criteria and were, therefore, reviewed in the present study. The six studies showed a reverse relationship between prolactin and progesterone, such that if one increases the other drops. Furthermore, Toxoplasmosis increased progesterone levels, which results in the suppression of prolactin levels. Thus, toxoplasmosis-induced progesterone secretion has an antagonistic effect on prolactin levels. Since prolactin strongly elicits innate and adaptive immune responses, toxoplasmosis-induced progesterone release dampens the immune response of the host and enhances susceptibility to severe toxoplasmosis.